Determinants of Sharia Financial Literacy: A Literature Review - Sapsuha, Mubasysyyratul Ummah; Awaluddin, Murtiadi (JAAF (Journal of Applied Accounting and Finance), 2024)
In some countries with large Muslim populations, the low level of financial literacy is also one of the things that deserves attention. This study aims to examine the factors that contribute to the low level of Sharia financial literacy and identify potential strategies to improve it. The method used is a systematic literature review of scientific articles published in the last ten years, focusing on empirical studies in Muslim-majority countries. The results of the review show that the low literacy of Sharia finance is caused by several main factors, including the lack of formal education about the concept and products of Sharia finance, the complexity of Sharia financial products that are difficult for the general public to understand, limited access to Sharia financial institutions in some regions, and the emergence of negative perceptions or misconceptions about the Sharia financial system. In addition, psychological factors, consumer behavior, government policies and regulations, and technology still need to be studied more deeply whether there are indications in determining Sharia financial literacy. Therefore, further research is needed to measure the effectiveness of these interventions in different cultural and socioeconomic contexts.